Residue to rations: Enhancing livestock nutrition with agricultural byproducts - Papageorgiou, Maria; Karageorgou, Agori; Goliomytis, Michael; Tzamaloukas, Ouranios; Simitzis, Panagiotis E (My University, 2025)
A great quantity of waste is generated during processing by the agro-industry as a result of the increased demand for agricultural products by consumers worldwide. Agro-industrial byproducts can be utilized as alternatives to conventional feedstuffs in livestock nutrition, resulting in minimization of production cost and improvement of productivity, while contributing to environmental, social, and economic sustainability. These byproducts also contain several bioactive compounds that improve quality traits of the derived animal products, leading to the fortification of human health against nutrition-related diseases associated with the contemporary sedentary way of living. The potential of incorporating agro-industrial byproducts (e.g., apple pomace, citrus pulp, grape pomace, olive cake, pomegranate pulp, palm kernel cake, sugar beet pulp, tomato pomace) as functional ingredients into livestock diets, but also potential limitations of utilizing them in animal nutrition, are discussed in the present review. Proposed processing methods and proper developmental strategies could improve the nutritive value and facilitate the utilization of agro-industrial byproducts in animal production.
Keywords: Agro-industrial byproducts; Livestock production; Nutraceuticals; Sustainability; Antioxidants